PROSES EKSTRAKSI MINYAK DARI BIJI PEPAYA (CARICA PAPAYA) DENGAN MENGGUNAKAN PELARUT n-HEKSANA - Azhari Azhari; Nilva Mutia; Ishak Ishak (LPPM Universitas Malikussaleh, 2020)
Papaya is the most beneficial fruit for human health. In addition to the fruit that can be consumed, it turns out papaya seeds can also be used. In addition to the seeds used to be planted as well as only being waste, oil can also be obtained from papaya seeds. One method for obtaining papaya seed oil is a method of extracting heat (requires installation in the process), in general the notion of reflux is extraction with a solvent at its boiling temperature point, for a certain time and the amount of solvent adjusted to air temperature. In this research, papaya seed extraction was carried out, percent yield analysis was carried out, and heavy type analysis of papaya seed oil extraction was carried out. The purpose of this study was to study the variation in extraction time of papaya seeds with solvents on the yield of oil produced. This research was carried out by reacting papaya seeds with hexane solvents at 65 ℃. Where the weight of papaya seeds is 50 gr, and the volume of solvents varied by 300 ml, 400 ml, and 500 ml and the reaction time is 120 minutes, 150 minutes, and 180 minutes. The results showed that the largest papaya seed oil was 34.2% at a volume of 500 ml solvent for 180 minutes and a high density of 0.87 gr / ml at a volume of 500 ml solvent for 180 minutes.Keywords: Extraction, hexane, papaya seed oil, reflux